English as a Foreign Language Teachers’ Work Engagement, Burnout, and Their Professional Identity - Xing, Zhaopeng (Frontiers in Psychology, 2022)
Teacher-related variables have been considered as determining factors in shaping educational system. Teacher professional identity is also very important construct that affect teachers’ teaching practice Moreover, the positive and negative emotions are considered sporadically in Chinese English as a Foreign Language (EFL) educational contexts; however, and there is a paucity of research in investigating the relationship between work engagement as a positive emotion and teacher burnout as a negative workrelated factor. This review also tried to examine how teachers’ professional identity is affected by teachers’ positive and negative emotions in Chinese contexts. Earlier studies have verified that teacher burnout is significantly correlated with professional identity. The earlier investigations showed the mediating role of job resources, such as job satisfaction and obligation, in the correlation between teacher burnout and professional identity. Moreover, studies have shown a significant negative correlation between teacher burnout and work engagement. Some variables, including personal features, instructive environment, work difficulties, job capital, character strengths, self-efficacy, close relationship with school colleagues, and emotional intelligence, mediate the correlation between teacher burnout and work engagement. Finally, this review specified that teachers’ professional identity is regarded as a critical variable in fostering work engagement. Emotional intelligence was also considered a mediating variable that affected the relationship between teacher professional identity and work engagement. Moreover, the study has pedagogical implications and suggestions for different teacher educators, administrators, and advisors. The ideas can improve their awareness of teacher burnout, professional identity, and work engagement in instructive contexts.